Climate-specific health literacy in health professionals: an exploratory study - Albrecht, Lorenz; Reismann, Lydia; Leitzmann, Michael; Bernardi, Christine; von Sommoggy, Julia; Weber, Andrea; Jochem, Carmen (Frontiers in Medicine, 2023)
Background Health professionals such as physicians and nurses may play an important role in the transformation process towards a healthy, sustainable and climate-sensitive society. However, little is known about their climate-specific health literacy. This study aimed to assess knowledge regarding climate change and its impacts on health and climate-specific health literacy in health professionals. Methods In July/August 2022, a cross-sectional, questionnaire-based study was carried out at the University Hospital Regensburg, Germany, to assess climate-specific health literacy in nurses and physicians from various clinical specialties. Descriptive and exploratory statistical analyses were performed. Results The study population consisted of 142 participants (57.7% women; response rate: 24,7%). Most participants (93%) considered climate change to be highly relevant. However, only 12% of respondents stated to be very well informed regarding the general consequences of climate change. Although 57% of all participants had never mentioned climate change in relation to health to their patients, participants with higher levels of knowledge regarding the effects of climate change were more likely to mention it compared to those with lower levels of knowledge. The most frequently stated obstacle to integrate the topic of climate change in clinical work was lack of time during work (79%), not enough information (42%) and lacking materials (39%). Differences between health professions were apparent. Conclusion The results of our survey suggest that the current state of climate-specific health literacy differs between different groups of health professionals. There is a need to improve health professionals’ levels of climate-specific health literacy and to increase the potential in interprofessional cooperation regarding planetary health.